Development of the National Institute for Occupational Safety and Health Worker Well-Being Questionnaire. Issue 8 (9th August 2022) - Chari, Ramya; Sauter, Steven L.; Petrun Sayers, Elizabeth L.; Huang, Wenjing; Fisher, Gwenith G.; Chang, Chia-Chia
Abstract : The NIOSH WellBQ has direct population and occupational health significance, with indirect significance for clinical practice. The instrument assesses multiple components of well-being spanning the work environment and conditions outside of work that can provide context for health conditions presented by workers. Abstract : Objective: This article describes development of the National Institute for Occupational Safety and Health (NIOSH) Worker Well-Being Questionnaire (WellBQ). Methods: The NIOSH WellBQ was developed through literature reviews and expert panel recommendations. We drew from a representative sample of the civilian, noninstitutionalized, US working population to pilot the questionnaire. Psychometric analyses were performed on data from 975 respondents to finalize items and optimize the NIOSH WellBQ's psychometric properties. Results: The final questionnaire consists of 16 scales, 5 indices, and 31 single items across 5 domains: (1) work evaluation and experience; (2) workplace policies and culture; (3) workplace physical environment and safety climate; (4) health status; and (5) home, community, and society (experiences and activities outside of work). The instrument demonstrated adequate reliability and validity. Conclusions: The NIOSH WellBQ is a reliable and valid instrument that comprehensively measures worker well-being.